2016
DOI: 10.1515/cclm-2016-0709
|View full text |Cite
|
Sign up to set email alerts
|

Assuring the quality of interpretative comments in clinical chemistry

Abstract: Abstract:The provision of interpretative advice on laboratory results is a post-analytic activity and an integral part of clinical laboratory services. It is valued by healthcare workers and has the potential to prevent or reduce errors and improve patient outcomes. It is important to ensure that interpretative comments provided by laboratory personnel are of high quality: comments should be patientfocused and answer the implicit or explicit question raised by the requesting clinician. Comment providers need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…The values of simultaneous measurement of an analyte in the serum/plasma and synovial fluid ( e.g. glucose) should be reported on the same test report ( 15 , 48 ). Decision limits and/or reference intervals for clinically useful analytes in SF laboratory testing are provided throughout this document and should be implemented on the test report (summarized in Table 3 ).…”
Section: Postanalytical Phasementioning
confidence: 99%
“…The values of simultaneous measurement of an analyte in the serum/plasma and synovial fluid ( e.g. glucose) should be reported on the same test report ( 15 , 48 ). Decision limits and/or reference intervals for clinically useful analytes in SF laboratory testing are provided throughout this document and should be implemented on the test report (summarized in Table 3 ).…”
Section: Postanalytical Phasementioning
confidence: 99%
“…Comments are added only to improve the clinical value of the results and influence further diagnostic procedures or differential diagnosis; comments that do not provide additional value to the results should be avoided. Table 2 describes the minimum required content of a laboratory test report ( 16 , 42 - 45 ).…”
Section: Procedures 3: Preparation Of the Laboratory Test Reportmentioning
confidence: 99%
“…Recent survey among diagnostic laboratories in Croatia showed that only small number of laboratories interprets the results of the coagulation test report or recommendations for further testing ( 6 ). Nowadays, as an integral part of laboratory service, laboratories are increasingly encouraged to provide interpretative and/or informative comments related to interferences and findings discovered by the laboratory for a particular patient´s sample ( 56 ). The interpretative and/or informative comments attached to the result report may help the clinician to appropriately use the laboratory information.…”
Section: Postanalytical Phase In Coagulation Testingmentioning
confidence: 99%